2010
DOI: 10.1002/anie.201002060
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Flexible Transformation of Biomass‐Derived Platform Chemicals by a Multifunctional Catalytic System

Abstract: A sustainable supply chain: The controlled transformation of the biomass‐derived platform compounds levulinic acid (LA) and itaconic acid (IA) into the corresponding lactones, diols, or cyclic ethers (see picture) by using a multifunctional molecular catalyst is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
406
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 562 publications
(425 citation statements)
references
References 39 publications
10
406
2
3
Order By: Relevance
“…[19][20][21] This system has drawbacks of non-reusability, special handling of metal complexes and high cost of phosphine ligands. As a solution, Cao et al 22 found that 1,4-pentanediol can be produced by the selective hydrogenation of GVL over copper zirconia catalyst.…”
mentioning
confidence: 99%
“…[19][20][21] This system has drawbacks of non-reusability, special handling of metal complexes and high cost of phosphine ligands. As a solution, Cao et al 22 found that 1,4-pentanediol can be produced by the selective hydrogenation of GVL over copper zirconia catalyst.…”
mentioning
confidence: 99%
“…LA could be converted to S-GVL in moderate yields of 66% and with 98.5% ee at 60 o C, 60 bar H 2 in EtOH using a catalyst system generated in situ from [Ru(Me-allyl) 2 (COD)], S-BINAP and HCl. [28] Higher yields and ee where however achieved when EL was used as substrate, achieving 95% yields and 99% ee for S-GVL (table 1, entries [32][33]. Using the cheaper RuCl 3 as precursor in combination R-BINAP and HCl gave high yields of R-GVL (96%, ee 99%) from methyl levulinate under the same catalytic conditions (table 1, entry 34).…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 92%
“…[28][29][30][31] In early pioneering studies Osakada et al, [32] showed the activation of C-O bonds of five membered cyclic anhydride, aldehydic and keto acids using two different ruthenium ( [10] demonstrated the use of an in situ generated Ru catalyst using a combination of Ru(acac) 3 and the strongly electron donating phosphine P n Bu 3 in the presence of NH 4 PF 6 for LA hydrogenation to GVL ( [33] reported the effect of the mondentate and chelating phosphines: trioctylphosphine (P n Oct 3 ), 1,4-diphenylphosphinobutane (DPPB) and triphos ( fig. 2) and various acidic additives for the transformation of LA.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%
See 2 more Smart Citations